Carbon emissions and social capital in Sweden - French Association of Environmental and Resource Economists; Marbuah, George (FAERE, 2015)
"This paper addresses the issue of whether or not social capital explains per capita CO2 emissions dynamics in Swedish counties in an augmented environmental Kuznets curve framework. By accounting for issues of endogeneity in the presence of dynamic and spatial effects using geo-referenced emissions data, we show that per capita carbon emissions in a county matters for other counties and that net of economic, demographic and environmental factors, social capital has the potential to reduce carbon emissions in Sweden albeit less robustly. We test two different social capital constructs; trust in government and environmental engagement. Specifically, trust in the government inures to the reduction in CO2 emissions. Membership and engagement in environmental organisations reduces CO2 emissions only through its interaction with per capita income or trust. The implication of our estimates suggest that investment geared toward increasing the stock of social capital could inure to re ductions in CO2 emissions in addition to climate policy instruments in Sweden."